Inspiration in the Act of Reading: A Discussion of Ulrich H. J. Körtner's Hermeneutics. Issue 3 (September 2016) - Zeller, Kinga
Abstract: In German‐language theology, Professor Ulrich H. J. Körtner's theory of inspiration, as it relates to the Bible reader's perspective, is well known. His attempt to gain fruitful insights from contemporary literary hermeneutics while linking them to theological concerns makes his approach a valued yet not uncontroversial example of a reception‐aesthetics twist on the Lutheran sola Scriptura . This article presents Körtner's hermeneutical considerations with special regard to inspiration related to the Bible reader's perspective and shows how this approach may be related to some aspects of the crisis that the Lutheran churches and theology suffer today.